Challenges Faced by Healthcare Professionals During the COVID-19 Pandemic: A Qualitative Inquiry From Bangladesh - Razu, Shaharior Rahman; Yasmin, Tasnuva; Arif, Taimia Binte; Islam, Md. Shahin; Islam, Sheikh Mohammed Shariful; Gesesew, Hailay Abrha; Ward, Paul (Frontiers in Public Health, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has caused increasing challenges for healthcare professionals globally. However, there is a dearth of information about these challenges in many developing countries, including Bangladesh. This study aims to explore the challenges faced by healthcare professionals (Doctors and Nurses) during COVID-19 in Bangladesh. Methods: We conducted qualitative research among healthcare professionals of different hospitals and clinics in Khulna and Dhaka city of Bangladesh from May 2020 to August 2020. We conducted 15 in-depth telephone interviews using a snowball sampling technique. We used an in-depth interview guide as data were collected, audiotaped and transcribed. The data were analyzed both manually and using QDA Miner software as we used thematic analysis for this study. Results: Seven themes emerged from the study. Participants experienced higher workload, psychological distress, shortage of quality personal protective equipment (PPE), social exclusion/stigmatization, lack of incentives, absence of coordination and proper management during their service. These healthcare professionals faced difficulty coping with these challenges due to situational and organizational factors. They reported of faith in God and mutual support to be the keys to adapt to adversities. Adequate support to address the difficulties faced by healthcare professionals is necessary for an overall improved health outcome during the pandemic. Conclusion: The findings highlight the common challenges faced by health professionals during the COVID-19 outbreak. This implies the need to support adequate safety kits, protocols and support for both physical and mental health of the health professionals.